2008
DOI: 10.1016/j.yexcr.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol sensitizes melanomas to TRAIL through modulation of antiapoptotic gene expression

Abstract: Although many human melanomas express the death receptors TRAIL-R2/DR5 or TRAIL-R1/ DR4 on cell surface, they often exhibit resistance to exogenous TRAIL. One of the main contributors to TRAIL-resistance of melanoma cells is upregulation of transcription factors STAT3 and NF-κB that control the expression of antiapoptotic genes, including cFLIP and BclxL. On the other hand, the JNK-cJun pathway is involved in the negative regulation of cFLIP (a caspase-8 inhibitor) expression. Our observations indicated that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 51 publications
7
64
0
Order By: Relevance
“…Furthermore, RV by itself was an efficient inducer of apoptotic death in some cancer cell lines [28], including melanoma lines [17]. We observed that RV upregulated TRAIL gene promoter activity and induced TRAIL surface expression that was quite diverse in different melanoma lines (Fig.…”
Section: Effects Of Resveratrol (Rv) On Trail Surface Expression and mentioning
confidence: 66%
See 4 more Smart Citations
“…Furthermore, RV by itself was an efficient inducer of apoptotic death in some cancer cell lines [28], including melanoma lines [17]. We observed that RV upregulated TRAIL gene promoter activity and induced TRAIL surface expression that was quite diverse in different melanoma lines (Fig.…”
Section: Effects Of Resveratrol (Rv) On Trail Surface Expression and mentioning
confidence: 66%
“…Hence, RV via its effects on the main signaling pathways in melanoma cells resulting in strong downregulation of levels of antiapoptotic proteins, such as cFLIP-L (caspase-8 inhibitor) and Bcl-xL (Fig. 6c), can sensitize these cells to TRAIL-mediated apoptosis [17]. Knockdown of cFLIP levels by the specific RNAi also sensitizes SW1 cells to TRAIL-mediated apoptosis (data not shown).…”
Section: Effects Of Resveratrol (Rv) On Trail Surface Expression and mentioning
confidence: 90%
See 3 more Smart Citations